Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1101/2022.08.19.504606
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ROS are evolutionary conserved cell-to-cell signals

Abstract: Cell-to-cell communication is fundamental to multicellular organisms, as well as to unicellular organisms living in a microbiome. It is thought to have evolved as a stress- or quorum-sensing mechanism in unicellular organisms. A unique cell-to-cell communication mechanism that uses reactive oxygen species (ROS) as a signal (termed the ROS wave) was recently identified in flowering plants. This process is essential for systemic signaling and plant acclimation to stress and can spread from a small group of cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 76 publications
0
14
0
Order By: Relevance
“…Cell‐to‐cell communication can be found in films or microbiomes composed of unicellular organisms (Combarnous & Nguyen, 2020; Fichman et al, 2023). It is also at the foundation and origin of multicellular organisms.…”
Section: Evolution Of Cell‐to‐cell and Stomata‐to‐stomata Communicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell‐to‐cell communication can be found in films or microbiomes composed of unicellular organisms (Combarnous & Nguyen, 2020; Fichman et al, 2023). It is also at the foundation and origin of multicellular organisms.…”
Section: Evolution Of Cell‐to‐cell and Stomata‐to‐stomata Communicationmentioning
confidence: 99%
“…It is also at the foundation and origin of multicellular organisms. A recent study has shown that the ROS wave is a highly conserved cell‐to‐cell signal that can be found in communities of unicellular eukaryotes, plants from different lineages, monolayers of mammalian cells, and even organs of animals (Fichman et al, 2023). Basic cell‐to‐cell signals such as the ROS wave, electric wave and perhaps even the calcium wave could have therefore evolved to link different specialized cell types (e.g., different hair cells) with each other, as well as with other cell types, in a multicellular organism, very early on.…”
Section: Evolution Of Cell‐to‐cell and Stomata‐to‐stomata Communicationmentioning
confidence: 99%
“…ROS are chemically active compounds characterized by unpaired electrons and high oxygen content. They result in both cellular stress and the cellular immune response [ [89] , [90] , [91] , [92] ]. ROS in biological systems can arise from cellular oxidative metabolism or be generated by intracellular oxidases like cyclooxygenase and nicotinamide adenine dinucleotide phosphate oxidase [ [93] , [94] , [95] ].…”
Section: Role Of Nlrp3 In Pd Within Dopaminergic Neuronsmentioning
confidence: 99%
“…Many details of the processes involved in regeneration, repair and tumourigenesis are still unknown, particularly in mammals. The metabolic and cellular processes that are activated by damage are equivalent to those found in invertebrates and lower vertebrates and are mediated in a lesser or greater degree by processes that involve oxidation-reduction reactions triggering oxidative stress (Fichman et al, 2023;Rennolds & Bely, 2023;Seifert et al, 2023).…”
Section: Mechanisms Regeneration Repair or Tumourigenesis And Evolutionmentioning
confidence: 99%
“…There is a prevalence of glycolysis and pentose phosphate pathway during regeneration in amphibians (Varela-Rodriguez et al, 2020). ROS are early signals that play an essential role during tissue regeneration across the animal kingdom by regulating transcription factors via redox modifications (Fichman et al, 2023). ROS levels are controlled, and low levels stimulate proliferation or promote differentiation of different types of cells, whereas higher levels favour growth arrest; even, pathological high levels of ROS are cytotoxic.…”
Section: Metabolism and Redox-balancementioning
confidence: 99%